Quietness beyond Political Power: Politics of Taking Sanctuary (Bast Neshini) in the Shi'ite Shrines of Iran. Issue 3 (3rd May 2016) - Eshaghi, Peyman
Abstract : "The politic" and "the religious" have had many relations with each other in Iranian history and in some cases "the religious" has been defined in a situation beyond the extent of the political power. A case in point is the right of taking sanctuary in Shi'ite shrines. Throughout Iran's history, subjects could take refuge in Shi'ite shrines and some other places related to religious and non-religious authorities. Persecution was delayed or the individual was forgiven, though sometimes they were sentenced when exiting the shrine. By referring to religious texts that have reinforced that tradition, this article seeks to trace continuities between early Islam and modern Iran. It focuses on sanctuary taking and sit-ins at shrines and tombs, and on the interplay between those actions and political power, and discusses the changing mobility and dynamisms of those actions at different periods of Iranian history.